Secondary battery and electronic device
By designing a multi-layer structure in the negative electrode sheet of the secondary battery, using silicon-based particles, carbon-based particles and the first particle containing lanthanum, titanium and oxygen, combined with graphite particles, the electron transport network and ion channels are optimized, and the problem of deterioration of kinetic performance caused by energy density improvement in the prior art is solved, and high energy density, excellent rate discharge performance and extended cycle life are achieved.
Patent Information
- Application Number
- CN202411957453.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-08
AI Technical Summary
While the prior art increases the energy density of secondary batteries, it often leads to deterioration of kinetic performance and rate discharge performance, making it difficult to take into account both high energy density and excellent rate discharge performance.
By designing a multi-layer structure in the negative electrode sheet of the secondary battery, it includes a negative current collector, a first material layer and a second material layer. The first material layer is composed of silicon-based particles, carbon-based particles and first particles containing lanthanum, titanium and oxygen. The second material layer is composed of graphite particles. By controlling the proportion and structure of the materials of each layer, the electron transport network and ion channels are optimized, and the kinetic performance and cycle life are improved.
The high energy density, excellent rate discharge performance and extended cycle life of the secondary battery are achieved, and the problem of deterioration of kinetic performance caused by the increase in energy density in the prior art is solved.
Smart Images

Figure BDA0005216660360000201 
Figure BDA0005216660360000211 
Figure BDA0005216660360000221
Abstract
Description
Technical Field
[0001] The present application relates to the field of energy storage technology, and in particular to a secondary battery and an electronic device. Background Art
[0002] As an important component of secondary batteries, the physical and chemical properties of electrodes are directly related to the performance of secondary batteries. Carbon-based materials are widely used as negative electrode materials for secondary batteries because of their good conductivity and low cost. Existing technical means improve the energy density of batteries by combining silicon and carbon negative electrode materials, but this often leads to the deterioration of kinetic performance, thereby causing the degradation of rate discharge performance. Therefore, it is imperative to provide silicon-carbon negative electrode batteries with better rate discharge performance. Summary of the invention
[0003] In view of this, the embodiments of the present application provide a secondary battery and an electronic device, wherein the secondary battery has a silicon-carbon composite negative electrode with a higher energy density and better rate discharge performance and cycle life.
[0004] In a first aspect, an embodiment of the present application provides a secondary battery, which includes a negative electrode plate, a positive electrode plate, a separator and an electrolyte, wherein the negative electrode plate includes a negative electrode current collector, a first material layer and a second material layer. The first material layer includes silicon-based particles, carbon-based particles and first particles, and the first particles include lanthanum, titanium and oxygen. The second material layer is disposed between the negative electrode current collector and the first material layer; the second material layer includes graphite particles.
[0005] Based on the secondary battery of the embodiment of the present application, the surface of the negative electrode graphite material layer is coated with a first material layer containing silicon-based particles and carbon-based particles to improve the energy density, and the graphite material in the second material layer and the carbon-based particles in the first material layer jointly construct an electron transmission network, which can improve the electron transmission capacity of the negative electrode. On this basis, the inventors found that when the first material layer further includes first particles, on the one hand, it can be dispersed on the surface of the silicon-based particles, construct internal ion channels, accelerate ion conduction, improve the deterioration of the pole piece dynamics caused by the need for more binders in the silicon-carbon composite negative electrode, and improve the rate discharge performance; on the other hand, it can also delay the volume expansion of the silicon material during the cycle, thereby improving the cycle life.
[0006] In some embodiments, based on the mass of the first material layer, the mass proportion of the first particles is A%, and 0.05≤A≤2. Based on the above embodiments, the present application can further accelerate ion conduction, improve rate discharge performance, inhibit volume expansion of silicon materials during cycling, and improve cycle life by controlling the mass proportion of the first particles in the first material layer within the above range.
[0007] In some embodiments, based on the mass of the first material layer, the mass percentage of the lanthanum element is B%, 0.022≤B≤0.88. Based on the above embodiments, the present application can further improve the electrode dynamics, improve the rate discharge performance, and delay the volume expansion of the silicon material during the cycle process by controlling the mass percentage of the lanthanum element in the first material layer within the above range, thereby improving the cycle life.
[0008] In some embodiments, based on the mass of the first material layer, the mass percentage of silicon is C%, N=B / C×10 4 , 4.4≤N≤586.7, preferably 20≤N≤200. Based on the above embodiments, the present application can further improve the energy density, enhance the electrode dynamics, improve the rate discharge performance, and delay the volume expansion of the silicon material during the cycle process, thereby improving the cycle life by controlling the mass ratio of the lanthanum element and the mass ratio of the silicon element in the first material layer within the above range.
[0009] In some embodiments, the surface of the negative electrode plate includes a test area. Based on the area of the test area, the projected area of the silicon-based particles along the direction perpendicular to the test area is S. 1 μm 2 , the projected area of the carbon-based particles is S 2 μm 2 , S=S 1 / S 2 , 1.68≤S≤100. Based on the above embodiments, the present application can further improve the electrode dynamics, improve the rate discharge performance, and delay the volume expansion of the silicon material during the cycle process, thereby improving the cycle life by limiting the number of silicon-based particles and carbon-based particles in the first material layer of the negative electrode plate within a suitable range.
[0010] In some embodiments, the thickness of the first material layer is H 1 μm, the thickness of the second material layer is H 2 μm, H=H 1 / (H 1 +H 2 ), 0.1≤H≤0.75, preferably 0.33≤H≤0.67. Based on the above embodiments, the present application can further improve the energy density, enhance the electrode dynamics, improve the rate discharge performance, and delay the volume expansion of the silicon material during the cycle, thereby improving the cycle life by controlling the thickness of the first material layer and the second material layer of the negative electrode plate within a suitable range.
[0011] In some embodiments, the first material layer and the second material layer include a binder. Based on the mass of the negative electrode plate, the mass content of the binder in the first material layer is 1.2% to 12.8%, and the mass content of the binder in the second material layer is 0.5% to 2.2%. Based on the mass of the negative electrode plate, the mass proportion of the binder in the first material layer is K%, and the mass proportion of the binder in the second material layer is J%, 0.55≤K / J≤25.6, preferably 1.5≤K / J≤16. In some embodiments, the binder in the first material layer includes polyacrylic acid, and the binder in the second material layer includes styrene-butadiene rubber or carboxymethyl cellulose. Based on the above embodiments, the present application controls the mass ratio of the binder in the first material layer and the second material layer of the negative electrode plate within the above range, so that the amount of binder in the first material layer and the second material layer is in a suitable range, which can not only improve the dynamic level of the plate and thus improve the rate discharge performance, but also alleviate the volume expansion of the silicon material during the cycle, thereby taking into account the improvement of the cycle life.
[0012] In some embodiments, the secondary battery satisfies at least one of the following conditions: (1) the silicon-based particles include a carbon carrier, elemental silicon and a carbon coating layer, and the elemental silicon is distributed on the surface and inside of the carbon carrier; (2) the carbon-based particles include at least one of graphite or hard carbon; (3) the first particles include Li x La (2-x) / 3 TiO 3 , 0.1≤x≤0.3; based on the above embodiments, the present application can improve the energy density by adopting silicon-based particles with the above structure; the carbon-based particles are selected from graphite or hard carbon to improve the cycle stability and electrode dynamics; the first particle of the above chemical formula can improve the internal dynamics of the electrode; the first particle includes the above-mentioned element blending, which can improve the ion conduction of the solid electrolyte itself, improve the dynamics, and improve the intrinsic stability of the material; when the secondary battery of the present application meets the above conditions, it can further improve the rate discharge performance while improving the cycle life.
[0013] In some embodiments, the first particles further include a doping element, and the doping element includes at least one of niobium, zirconium, germanium, tantalum, lanthanum, sulfur, silicon, or fluorine. Based on the above embodiments, the present application further adds a doping element to the solid electrolyte, which can improve the rate discharge performance and cycle performance while suppressing the expansion of the pole piece.
[0014] In some embodiments, the electrolyte includes fluoroethylene carbonate; based on the mass of the electrolyte, the mass proportion of fluoroethylene carbonate is E%, 2.2≤E≤13.5, preferably 5.5≤E≤11.5. Based on the above embodiments, the electrolyte of the secondary battery of the present application includes fluoroethylene carbonate, which can form a LiF-rich SEI during the battery cell cycle. On the one hand, it can increase the ion transmission speed in the electrode, and on the other hand, it can reduce the side reactions during the electrode cycle, thereby improving the rate discharge performance while improving the cycle life.
[0015] In some embodiments, the electrolyte includes lithium nitrate, and the mass percentage of lithium nitrate is F%, 0.1≤F≤8.8, based on the mass of the electrolyte. Based on the above embodiments, the electrolyte of the secondary battery of the present application includes lithium nitrate, which can form a Li-rich electrolyte during the battery cell cycle. 3 SEI of N, Li 3 N has extremely high ion conductivity, which can accelerate lithium ion conduction, thereby further improving rate discharge performance while also improving cycle life.
[0016] In some embodiments, both the positive electrode sheet and the negative electrode sheet are provided with a pole ear; the positive electrode sheet, the separator and the negative electrode sheet are stacked in sequence and then wound to form an electrode assembly, with the thickness direction of the electrode assembly as the first direction; the negative electrode sheet is provided with a first adhesive tape and a second adhesive tape, and the positive electrode sheet is provided with a third adhesive tape; the first adhesive tape is provided on at least part of the surface of the negative electrode ear, and the third adhesive tape is provided on at least part of the surface of the positive electrode ear; the projection of the second adhesive tape along the first direction overlaps at least part of the projection of the positive electrode ear along the first direction. Based on the above embodiments, the present application can improve the problem of reduced cohesion of the electrode sheet caused by the large difference in specific surface area of the particles added to the negative electrode material layer and the uneven adsorption force on the binder by providing the above second adhesive tape, thereby improving the rate discharge performance while taking into account the improvement of the cycle life.
[0017] In some embodiments, the sum of the areas of the first adhesive tape and the second adhesive tape is P 1 cm 2 , the area of the first material layer is P 2 cm 2 , P = 100 × P 1 / P 2 , 0.3≤P≤6. Based on the above embodiments, the present application can further improve the problem of reduced electrode cohesion due to uneven adsorption of the binder and large differences in the specific surface areas of the particles added to the negative electrode material layer by controlling the ratio of the sum of the areas of the first adhesive tape and the second adhesive tape to the area of the first material layer within the above range, thereby improving the rate discharge performance while also improving the cycle life.
[0018] In a second aspect, an embodiment of the present application provides an electronic device, which includes the above-mentioned secondary battery. DETAILED DESCRIPTION
[0019] In order to make the purpose, technical solution and advantages of the present application more clear, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described here are only used to explain the present application and are not used to limit the present application.
[0020] A first aspect of an embodiment of the present application provides a secondary battery, including a negative electrode, a positive electrode, an electrolyte and a separator.
[0021] negative electrode
[0022] The negative electrode includes a negative electrode plate, which includes a negative electrode current collector, a first material layer and a second material layer. The first material layer includes silicon-based particles, carbon-based particles and first particles, and the first particles include lanthanum, titanium and oxygen. The second material layer is arranged between the negative electrode current collector and the first material layer; the second material layer includes graphite particles. The surface of the negative electrode graphite material layer is coated with a first material layer containing silicon-based particles and carbon-based particles to improve the energy density. The graphite material in the second material layer and the carbon-based particles in the first material layer jointly construct an electron transmission network, which can improve the electron transmission capacity of the negative electrode. On this basis, when the first material layer further includes the first particles, it can accelerate ion conduction, improve rate discharge performance, and increase cycle life.
[0023] In some embodiments, based on the mass of the first material layer, the mass percentage of the first particles is A%, 0.05≤A≤2. For example, based on the mass of the first material layer, the mass percentage of the first particles can be 0.05, 0.17, 0.50, 0.67, 1.10, 1.19, 1.20, 1.30, 1.42, 1.93, 2.00, or a value in the range of any two of these values. Controlling the mass percentage of the first particles in the first material layer within the above range can further accelerate ion conduction, improve rate discharge performance, inhibit volume expansion of silicon materials during cycling, and improve cycle life.
[0024] In some embodiments, based on the mass of the first material layer, the mass percentage of the lanthanum element is B%, 0.022≤B≤0.88. For example, based on the mass of the first material layer, the mass percentage of the lanthanum element can be 0.022, 0.07, 0.08, 0.15, 0.22, 0.29, 0.40, 0.48, 0.52, 0.53, 0.62, 0.79, 0.88 or a value within the range formed by any two of these values. Controlling the mass percentage of the lanthanum element in the first material layer within the above range can further improve the electrode dynamics, improve the rate discharge performance, and delay the volume expansion of the silicon material during the cycle, thereby improving the cycle life.
[0025] In some embodiments, based on the mass of the first material layer, the mass percentage of silicon is C%, N=B / C×10 4 , 4.4≤N≤586.7, preferably 20≤N≤200. For example, based on the mass of the first material layer, the ratio of the mass proportion of the lanthanum element to the mass proportion of the silicon element can be 4.4, 6.6, 11.0, 20.0, 37.4, 50.0, 110.0, 146.7, 147.4, 176.0, 185.7, 200.0, 312.4, 440.0, 550.0, 586.7 or a value within the range composed of any two of these values. Controlling the mass proportion of the lanthanum element and the mass proportion of the silicon element in the first material layer within the above range can further improve the energy density, enhance the electrode dynamics, improve the rate discharge performance, and delay the volume expansion of the silicon material during the cycle, thereby taking into account the improvement of the cycle life.
[0026] In some embodiments, the surface of the negative electrode plate includes a test area. Based on the area of the test area, the projected area of the silicon-based particles along the direction perpendicular to the test area is S. 1 μm 2 , the projected area of the carbon-based particles is S 2 μm 2 , S=S 1 / S 2 , 1.68≤S≤100. For example, based on the area of the region to be measured, the ratio of the cross-sectional area of the silicon-based particles to the cross-sectional area of the carbon-based particles can be 1.68, 10.14, 40.15, 44.34, 69.37, 100.00, or a value within the range formed by any two of these values. Limiting the number of silicon-based particles and carbon-based particles in the first material layer of the negative electrode to a suitable range can further improve the electrode dynamics, improve the rate discharge performance, and delay the volume expansion of the silicon material during the cycle, thereby improving the cycle life.
[0027] In some embodiments, the thickness of the first material layer is H1 μm, the thickness of the second material layer is H 2 μm, H=H 1 / (H 1 +H 2 ), 0.1≤H≤0.75, preferably 0.33≤H≤0.67. For example, the value of H can be 0.10, 0.22, 0.33, 0.48, 0.49, 0.50, 0.53, 0.57, 0.67, 0.75 or a value in the range formed by any two of these values. Controlling the thickness of the first material layer and the second material layer of the negative electrode within a suitable range can further improve the energy density, enhance the electrode dynamics, improve the rate discharge performance, and delay the volume expansion of the silicon material during the cycle, thereby improving the cycle life.
[0028] In some embodiments, the first material layer and the second material layer include a binder. Based on the mass of the negative electrode sheet, the mass content of the binder in the first material layer is 1.2% to 12.8%. For example, the mass content of the binder in the first material layer can be 1.2%, 1.5%, 2.4%, 3.9%, 4.0%, 6.2%, 7.2%, 8.0%, 8.5%, 12.8%, or a value within the range of any two of these values. The mass content of the binder in the second material layer is 0.5% to 2.2%. For example, the mass content of the binder in the second material layer can be 0.5%, 0.63%, 0.7%, 0.8%, 1.0%, 1.1%, 1.3%, 1.5%, 1.9%, 2.2%, or a value within the range of any two of these values. Based on the mass of the negative electrode sheet, the mass proportion of the binder in the first material layer is K%, and the mass proportion of the binder in the second material layer is J%, 0.55≤K / J≤25.6, preferably 1.5≤K / J≤16. For example, based on the mass of the negative electrode sheet, the ratio of the mass proportion of the binder in the first material layer to the mass proportion of the binder in the second material layer can be 0.55, 0.66, 1.50, 2.40, 6.00, 7.75, 8.00, 8.50, 14.12, 16.00, 19.10, 25.60 or a value within the range of any two of these values. In some embodiments, the binder in the first material layer includes polyacrylic acid, and the binder in the second material layer includes styrene-butadiene rubber or carboxymethyl cellulose. By selecting the above-mentioned binder and controlling the mass ratio of the binder in the first material layer and the second material layer of the negative electrode plate within the above-mentioned range, the amount of binder in the first material layer and the second material layer can be within a suitable range, which can not only improve the dynamic level of the electrode plate and thus improve the rate discharge performance, but also alleviate the volume expansion of the silicon material during the cycle process, thereby improving the cycle life.
[0029] In some embodiments, the secondary battery satisfies at least one of the following conditions: (1) the silicon-based particles include a carbon carrier, elemental silicon and a carbon coating layer, wherein the elemental silicon is distributed on the surface and inside of the carbon carrier; (2) the carbon-based particles include at least one of graphite or hard carbon; (3) the first particles include Li x La (2-x) / 3 TiO 3 , 0.1≤x≤0.3, for example, the value of x can be 0.1, 0.2, 0.3 or a value in the range of any two of these values. When the secondary battery of the present application meets the above conditions, the rate discharge performance can be further improved while improving the cycle life.
[0030] In some embodiments, the first particles further include a doping element, and the doping element includes at least one of niobium, zirconium, germanium, tantalum, lanthanum, sulfur, silicon, or fluorine. Further adding doping elements to the solid electrolyte can improve rate discharge performance and cycle performance while suppressing the expansion of the pole piece.
[0031] In some of these embodiments, the charge capacity of the negative electrode active material is greater than the discharge capacity of the positive electrode active material to prevent lithium metal from being unintentionally deposited on the negative electrode during charging.
[0032] The negative electrode material layer of the present application also includes a conductive agent. The present application has no particular restrictions on the type of the negative electrode conductive agent, as long as the purpose of the present application can be achieved. For example, the negative electrode conductive agent can be at least one of acetylene black, Ketjen black, carbon nanotubes, carbon fibers, carbon dots or graphene, and the above-mentioned carbon nanotubes can include but are not limited to at least one of single-walled carbon nanotubes or multi-walled carbon nanotubes.
[0033] The present application has no particular restrictions on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the negative electrode current collector may include copper foil, aluminum foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam or a polymer substrate covered with a conductive metal, etc. Among them, the conductive metal includes but is not limited to copper, nickel or titanium, and the material of the polymer substrate includes but is not limited to at least one of polyethylene, polypropylene, ethylene propylene copolymer, polyethylene terephthalate, polyethylene naphthalate or poly(p-phenylene terephthalamide). In the present application, there is no particular restriction on the thickness of the negative electrode current collector and the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode current collector is 4μm to 12μm, and the thickness of the single-sided negative electrode material layer is 30μm to 160μm. In the present application, the negative electrode material layer can be arranged on one surface in the thickness direction of the negative electrode current collector, or on two surfaces in the thickness direction of the negative electrode current collector. It should be noted that the "surface" here can be the entire area of the negative electrode current collector or a partial area of the negative electrode current collector. This application has no special restrictions as long as the purpose of this application can be achieved.
[0034] The present application has no particular restrictions on the compaction density of the negative electrode sheet, as long as the purpose of the present application can be achieved. For example, the compaction density of the negative electrode sheet can be 1.0 g / cm 3 Up to 1.85g / cm 3 The present application has no particular limitation on the cold pressing pressure of the negative electrode sheet, as long as the purpose of the present application can be achieved. For example, the cold pressing pressure of the negative electrode sheet can be 3 tons to 30 tons.
[0035] Optionally, the negative electrode plate may further include a conductive layer, which is located between the negative electrode current collector and the negative electrode material layer. The present application has no particular restrictions on the composition of the conductive layer, which may be a conductive layer commonly used in the art. The conductive layer includes a conductive agent and a binder. The present application has no particular restrictions on the conductive agent and the binder in the conductive layer, which may be at least one of the above conductive agent and the above binder. The present application has no particular restrictions on the mass ratio of the conductive agent and the binder in the conductive layer, and those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved. The present application has no particular restrictions on the thickness of the conductive layer, as long as the purpose of the present application can be achieved, for example, the thickness of the conductive layer is 1μm to 10μm.
[0036] positive electrode
[0037] The positive electrode includes a positive electrode current collector and a positive electrode material layer disposed on at least one surface of the positive electrode current collector. The positive electrode material layer includes a lithium-containing transition metal composite oxide, and the lithium-containing transition metal composite oxide includes Li w Na z Co 1-y M y O 2, wherein 0.6<w<0.95, 0≤y<0.15, 0<z≤0.03, and M is selected from at least one of the group consisting of Al, Mg, Ti, Mn, Fe, Ni, Zn, Cu, Nb, Cr and Zr. For example, the above subscripts may be 0.6<w<0.7, 0≤y<0.10, and 0<z<0.01; 0.7<w<0.8, 0.05<y<0.10, and 0<z<0.02; 0.8<w<0.9, 0.06<y<0.09, and 0<z≤0.03; 0.9<w<0.95, 0.07<y<0.08, and 0.01<z<0.02; 0.6<w<0.9, 0.08<y<0.15, and 0.01<z≤0.03. By adding the above-mentioned lithium-containing transition metal composite oxide to the positive electrode material layer in the electrochemical device, and controlling the content ratio of each metal atom in the lithium-containing transition metal composite oxide, especially controlling the content ratio of sodium atoms to meet the above-mentioned range, it is possible to improve both the high-temperature storage performance and the low-temperature discharge performance of the electrochemical device.
[0038] In some embodiments, the positive electrode material layer includes a positive electrode conductive material; the type of the positive electrode conductive material is not limited, and any known conductive material can be used. Examples of positive electrode conductive materials may include, but are not limited to, carbon black such as acetylene black and Super-P; amorphous carbon materials such as needle coke; carbon nanotubes; graphene, etc. The above positive electrode conductive materials may be used alone or in any combination.
[0039] In some embodiments, the positive electrode material layer includes a positive electrode binder; the type of the positive electrode binder is not particularly limited, and in the case of a coating method, any material that can be dissolved or dispersed in a liquid medium used in electrode manufacturing can be used. Examples of positive electrode binders may include, but are not limited to, one or more of the following: resin polymers such as polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, nitrocellulose, etc.; rubber polymers such as styrene-butadiene rubber, nitrile rubber, fluororubber, isoprene rubber, polybutadiene rubber, ethylene-propylene rubber, etc.; thermoplastic elastomer polymers such as styrene-butadiene-styrene block copolymers or their hydrides, ethylene-propylene-diene terpolymers, styrene-ethylene-butadiene-ethylene copolymers, styrene-isoprene-styrene block copolymers or their hydrides; soft resin polymers such as syndiotactic-1,2-polybutadiene, polyvinyl acetate, ethylene-vinyl acetate copolymers, propylene-α-olefin copolymers; fluorine polymers such as polyvinylidene fluoride, polytetrafluoroethylene, fluorinated polyvinylidene fluoride, polytetrafluoroethylene-ethylene copolymers; polymer compositions having ion conductivity of alkali metal ions, etc. The above positive electrode binders may be used alone or in any combination.
[0040] There is no limitation on the type of solvent used to form the positive electrode slurry, as long as it is a solvent that can dissolve or disperse the positive electrode active material, the conductive material, the positive electrode binder, and the thickener used as needed. Examples of solvents used to form the positive electrode slurry may include any of aqueous solvents and organic solvents. Examples of aqueous media may include, but are not limited to, a mixed medium of alcohol and water or water, etc. Examples of organic media may include, but are not limited to, aliphatic hydrocarbons such as hexane; aromatic hydrocarbons such as benzene, toluene, xylene, methylnaphthalene; heterocyclic compounds such as quinoline and pyridine; ketones such as acetone, methyl ethyl ketone, and cyclohexanone; esters such as methyl acetate and methyl acrylate; amines such as diethylenetriamine and N,N-dimethylaminopropylamine; ethers such as diethyl ether, propylene oxide, and tetrahydrofuran; amides such as N-methylpyrrolidone, dimethylformamide, and dimethylacetamide; aprotic polar solvents such as hexamethylphosphoramide and dimethyl sulfoxide, etc.
[0041] Thickeners are generally used to adjust the viscosity of the slurry. In the case of using an aqueous medium, the thickener and styrene-butadiene rubber emulsion can be used for slurrying. The type of thickener is not particularly limited, and examples thereof may include, but are not limited to, carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein, and salts thereof. The above thickeners may be used alone or in any combination.
[0042] The type of positive electrode current collector is not particularly limited, and it can be any material known to be suitable for use as a positive electrode current collector. Examples of positive electrode current collectors may include, but are not limited to, metal materials such as aluminum, stainless steel, nickel plating, titanium, tantalum, and materials such as carbon cloth and carbon paper. In some embodiments, the positive electrode current collector is a metal material. In some embodiments, the positive electrode current collector is aluminum.
[0043] In order to reduce the electronic contact resistance between the positive electrode current collector and the positive electrode material layer, the surface of the positive electrode current collector may include a conductive additive or a conductive coating. Examples of conductive additives may include, but are not limited to, carbon and precious metals such as gold, platinum, and silver. Examples of conductive coatings may include a mixture layer containing an inorganic oxide, a conductive agent, and a binder.
[0044] Electrolyte
[0045] The electrolytic solution used in the secondary battery of the present application includes an electrolyte and a non-aqueous solvent that dissolves the electrolyte.
[0046] In some embodiments, the electrolyte includes fluoroethylene carbonate. Based on the mass of the electrolyte, the mass proportion of fluoroethylene carbonate is E%, 2.2≤E≤13.5, preferably 5.5≤E≤11.5. For example, the mass proportion of fluoroethylene carbonate in the electrolyte can be 2.2, 3.4, 5.5, 6.5, 7.40, 10.30, 11.50, 13.5 or a value within the range composed of any two of these values. Including fluoroethylene carbonate in the electrolyte can form a LiF-rich SEI during the battery cell cycle. On the one hand, it can increase the ion transfer rate in the electrode, and on the other hand, it can reduce the side reactions during the electrode cycle, thereby improving the rate discharge performance while improving the cycle life.
[0047] In some embodiments, the electrolyte includes lithium nitrate. Based on the mass of the electrolyte, the mass percentage of lithium nitrate is F%, 0.1≤F≤8.8. For example, the mass percentage of lithium nitrate in the electrolyte can be 0.1, 0.9, 2.9, 4.4, 4.9, 6.9, 8.8 or a value in the range of any two of these values. The electrolyte of the secondary battery includes lithium nitrate, which can form a Li-rich electrolyte during the battery cell cycle. 3 SEI of N, Li 3 N has extremely high ion conductivity, which can accelerate lithium ion conduction, thereby further improving rate discharge performance while also improving cycle life.
[0048] The present application has no particular limitation on the type of lithium salt, as long as the purpose of the present application can be achieved. For example, the lithium salt may include but is not limited to lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ), lithium difluorophosphate (LiPO 2 F 2 ), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(oxalatoborate) (LiBOB) or lithium difluorooxalatoborate (LiDFOB). Based on the mass of the electrolyte, the mass proportion of the lithium salt can be 8% to 15%, for example, the mass proportion of the lithium salt can be 8%, 9%, 10%, 11%, 12.5%, 13%, 15% or a range consisting of any two of the values.
[0049] The present application has no particular restrictions on the types of the above-mentioned non-aqueous solvents, as long as the purpose of the present application can be achieved, for example, it may include but is not limited to at least one of carbonate compounds, carboxylate compounds, ether compounds or other organic solvents. The above-mentioned carbonate compounds may include but are not limited to at least one of chain carbonate compounds or cyclic carbonate compounds. The above-mentioned chain carbonate compounds may include but are not limited to at least one of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate or methyl ethyl carbonate. The above-mentioned cyclic carbonate compounds may include but are not limited to at least one of ethylene carbonate, propylene carbonate, butylene carbonate or ethylene ethylene carbonate. The above-mentioned carboxylate compounds may include but are not limited to at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decalactone, valerolactone or caprolactone. The above-mentioned ether compound may include but is not limited to at least one of ethylene glycol dimethyl ether, dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include but are not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate.
[0050] Diaphragm
[0051] In the present application, a diaphragm is usually provided between the positive electrode and the negative electrode, and the diaphragm is used to separate the positive electrode plate and the negative electrode plate to prevent internal short circuit of the secondary battery, allow electrolyte ions to pass freely, and do not affect the electrochemical charge and discharge process.
[0052] The present application has no particular restrictions on the separator, as long as the purpose of the present application can be achieved. For example, the material of the separator may include but is not limited to polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyester (e.g., polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex or aramid; the type of the separator may include at least one of woven membrane, non-woven membrane, microporous membrane, composite membrane, rolled membrane or spun membrane.
[0053] In the present application, the diaphragm may include a substrate and a surface treatment layer. The substrate may be a non-woven fabric or a composite film having a porous structure, and the material of the substrate may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used. Optionally, a surface treatment layer is provided on at least one surface of the substrate, and the surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. For example, the inorganic layer includes inorganic particles and a binder, and the present application has no particular restrictions on the above-mentioned inorganic particles, for example, it may include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application has no particular restrictions on the above-mentioned binder, for example, it may be at least one of the aforementioned binders. The polymer layer contains a polymer, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyvinyl pyrrolidone, polyvinyl ether, polyvinylidene fluoride or poly(vinylidene fluoride-hexafluoropropylene).
[0054] The pore size of the diaphragm in the present application is 0.01 μm to 1 μm, and the thickness is 5 μm to 50 μm. In some embodiments, the thickness of the diaphragm is greater than 1 μm, greater than 5 μm, or greater than 8 μm. In some embodiments, the thickness of the diaphragm is less than 50 μm, less than 40 μm, or less than 30 μm. When the thickness of the diaphragm is within the above range, the insulation and mechanical strength can be ensured, and the rate characteristics and energy density of the secondary battery can be ensured.
[0055] In some embodiments, both the positive electrode sheet and the negative electrode sheet are provided with a tab; the positive electrode sheet, the separator and the negative electrode sheet are stacked in sequence and then wound to form an electrode assembly, with the thickness direction of the electrode assembly as the first direction; the negative electrode sheet is provided with a first adhesive tape and a second adhesive tape, and the positive electrode sheet is provided with a third adhesive tape; the first adhesive tape is provided on at least part of the surface of the negative electrode tab, and the third adhesive tape is provided on at least part of the surface of the positive electrode tab; the projection of the second adhesive tape along the first direction overlaps at least part of the projection of the positive electrode tab along the first direction. By providing the above-mentioned second adhesive tape, the problem of reduced cohesion of the electrode sheet caused by the large difference in specific surface area of the particles added in the negative electrode material layer and the uneven adsorption force on the binder can be improved.
[0056] In some embodiments, the sum of the areas of the first adhesive tape and the second adhesive tape is P 1 cm 2 , the area of the first material layer is P 2 cm 2 , P = 100 × P 1 / P 2 , 0.3≤P≤6. For example, the ratio of the sum of the areas of the first adhesive tape and the second adhesive tape to the area of the first material layer can be 0.3, 0.4, 1.6, 2.9, 3.6, 4.5, 5.5, 6 or a value in the range formed by any two of these values. By controlling the ratio of the sum of the areas of the first adhesive tape and the second adhesive tape to the area of the first material layer within the above range, the problem of reduced cohesion of the electrode sheet caused by uneven adsorption of the binder due to large differences in the specific surface areas of the particles added to the negative electrode material layer can be further improved, thereby improving the rate discharge performance while also improving the cycle life.
[0057] The present application also provides an electronic device, which includes the secondary battery of the present application. The electronic device includes but is not limited to a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini CD, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.
[0058] Example
[0059] Hereinafter, taking lithium-ion batteries as an example, examples and comparative examples are given to more specifically describe the implementation of the secondary battery of the present application. Those skilled in the art will understand that the preparation method described in the present application is only an example, and any other suitable preparation method is within the scope of the present application. Various tests and evaluations are carried out according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.
[0060] Example 1-1
[0061] 1. Preparation of positive electrode
[0062] The positive electrode active material lithium cobalt oxide, the conductive agent conductive carbon black, and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 95:2:3, N-methylpyrrolidone (NMP) is added, and the mixture is stirred evenly under the action of a vacuum mixer to obtain a positive electrode slurry with a solid content of 70wt%. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 9μm, and dried to obtain a positive electrode sheet coated with a positive electrode material layer on one side. Repeat the above steps on the other surface of the positive electrode current collector aluminum foil to obtain a positive electrode sheet coated with a positive electrode material layer on both sides. By adjusting the pressure of the cold pressing, positive electrode sheets with different compaction densities and surface roughness can be obtained. After cold pressing, striping, and welding of the pole ears, a third adhesive tape is pasted on the surface of the pole ears, and dried to obtain a positive electrode sheet with a specification of 74mm×867mm.
[0063] 2. Preparation of electrolyte
[0064] In a dry argon atmosphere glove box, diethyl carbonate was used as the base solvent, and lithium hexafluorophosphate (LiPF 6 ) is dissolved in the above-mentioned base solvent, and vinylene carbonate and fluoroethylene carbonate are added to obtain an electrolyte. Wherein, based on the total mass of the electrolyte, LiPF 6 The mass proportion of tantalum is 12.5%, the mass proportion of vinylene carbonate is 2%, and the mass proportion of fluoroethylene carbonate is 7%.
[0065] 3. Preparation of negative electrode
[0066] <Preparation of negative electrode sheet>
[0067] (1) The negative electrode active materials, graphite particles, styrene-butadiene rubber (SBR), and carboxymethyl cellulose (CMC) are mixed in a mass ratio of 98.7:0.5:0.8, and then deionized water is added as a solvent and stirred evenly to prepare a second slurry with a solid content of 45wt%. The second slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 10μm to obtain a negative electrode sheet coated with a second material layer on one side; the above steps are repeated on the other surface of the negative electrode current collector copper foil to obtain a negative electrode sheet coated with a second material layer on both sides;
[0068] (2) The negative electrode active material (mass ratio of silicon carbon: hard carbon: graphite = 32:20:48), polyacrylonitrile (PAA), carbon nanotubes (CNT), the first particle (Li x La (2-x) / 3 TiO 3, wherein x = 0.11) are mixed in a mass ratio of 97.97:1.2:0.8:0.03, and then deionized water is added as a solvent and stirred evenly to prepare a first material layer slurry with a solid content of 45wt%. The first material layer slurry is evenly coated on one surface of the negative electrode sheet obtained in step (1); the above steps are repeated on the other surface of the negative electrode sheet to obtain a negative electrode sheet coated with the first material layer and the second material layer on both sides;
[0069] (3) After cold pressing, stripping, and welding of the tabs, a first adhesive tape is pasted on the surface of the tabs and dried to obtain a negative electrode sheet with a specification of 76.6 mm×875 mm.
[0070] 4. Preparation of diaphragm
[0071] A porous polyethylene film with a thickness of 15 μm was used as the separator.
[0072] 5. Preparation of lithium-ion batteries
[0073] Stack the positive electrode sheet, negative electrode sheet and separator in order, place the separator between the positive electrode sheet and the negative electrode sheet to play a role of isolation, stick the second adhesive tape on the negative electrode sheet, and wind it to obtain the electrode assembly. After winding, the projection of the second adhesive tape along the thickness direction of the electrode assembly overlaps with the projection of the positive electrode ear along the thickness direction of the electrode assembly. Place the electrode assembly in a packaging bag, remove moisture at 80°C, inject the above-mentioned electrolyte and package it. After the process of formation hot pressing, degassing, trimming and other processes, a lithium-ion battery is obtained.
[0074] 6. Test methods
[0075] (1) Element content and particle quality test method
[0076] Take a lithium-ion battery and discharge it at a constant current of 0.5C to 2.8V to obtain a fully discharged battery. Remove the negative electrode plate and analyze the cross-section of the plate along the thickness direction using energy dispersive X-ray analysis. The mass proportions of lanthanum, titanium and silicon in the first material layer are tested respectively, and the mass proportion of the first particles is calculated.
[0077] (2) Structural observation method
[0078] Take a lithium-ion battery, remove the negative electrode, polish it with argon ions and cut it open so that the entire cross section of the electrode along the thickness direction is exposed. Then use a scanning electron microscope to observe the crystal structure of the material in the electrode and measure the particle size and thickness of the material layer.
[0079] Take the lithium-ion battery, remove the negative electrode, polish it with argon ions, and then use a scanning electron microscope to observe the electrode and take pictures along the direction perpendicular to the electrode. Randomly select an area of 10880μm in the photo. 2The area is taken as the area to be tested in the embodiment of the present application, and the sum of the areas of the silicon-based particles and the sum of the areas of the carbon-based particles in the area to be tested are calculated respectively.
[0080] Instrument model: ZEISS SEM, accelerating voltage: 0.1 kV~30 kV.
[0081] (3) Test method for binder mass ratio
[0082] Take a lithium-ion battery, polish the negative electrode plate with argon ions and then cut it open so that the entire cross-section of the plate along the thickness direction is exposed, then use an infrared spectrometer (ATR IR spectrum) to test the absorption spectrum of the cross-section, analyze the binder distribution pattern along the thickness direction of the electrode to obtain the relative content of the binder in the first material layer and the relative content of the binder in the second material layer, and divide the two relative contents to obtain the mass proportion of the binder.
[0083] (4) Energy density test method
[0084] Take a lithium-ion battery, charge it to 4.5V at 0.2C rate at 25℃, then charge it at constant voltage until the current is less than or equal to 0.05C, and then discharge it to 2.8V at 0.2C rate, and test the lithium-ion battery 25℃ 0.2C rate discharge energy E; let it stand for 30min, charge it at 0.2C rate for 2.5h, and measure the cell thickness T and cell cross-sectional area S. Energy density Wh / L = E / (T×S).
[0085] (5) 4C rate discharge test
[0086] Take a lithium-ion battery, charge it to 4.5V at 0.2C rate at 25℃, then charge it to 0.05C at constant voltage, then let it stand for 30min, then discharge it to 2.8V at 0.2C rate, and test the lithium-ion battery 25℃ 0.2C rate discharge capacity; at 25℃, charge the lithium-ion battery to 4.5V at 0.2C rate, then charge it to 0.05C at constant voltage, then discharge it to 2.8V at 4C rate, and test the lithium-ion battery 4C rate discharge capacity. 4C rate discharge capacity retention rate % = 4C rate discharge capacity / 0.2C rate discharge capacity × 100%.
[0087] (6) Normal temperature cycle performance test: Place the lithium-ion battery in a 25°C constant temperature test box and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature. Charge it to 4.5V at a constant current of 1.3C, then charge it to a current of 0.025C at a constant voltage of 4.5V, let it stand for 5 minutes, and discharge it to 2.8V at a constant current of 0.5C. Record it as the initial discharge capacity C 0 Repeat this procedure for 500 cycles and record the discharge capacity C after 100 cycles. 1, calculate the cycle capacity retention rate of lithium-ion batteries.
[0088] Cycle capacity retention rate % = C 1 / C 0 ×100%.
[0089] The lithium ion batteries of the following embodiments or comparative examples are different from those of embodiment 1-1 only in that the mass proportions of the components are adjusted according to Table 1. The performance test results of the lithium ion batteries of the embodiments and comparative examples are shown in Table 1 below.
[0090] Table 1
[0091]
[0092]
[0093] *In the above table, the calculation results of N are rounded to 1 decimal place, and the calculation results of S are rounded to 2 decimal places.
[0094] As can be seen from Table 1, the lithium-ion batteries prepared in the embodiments of the present application have significantly improved rate discharge capacity retention performance and energy density of the lithium-ion batteries of Examples 1-1 to 1-20 relative to Comparative Example 1 in which the first material layer does not contain silicon-based particles. Relative to Comparative Example 2 in which the first material layer does not contain carbon-based particles, the rate discharge capacity retention performance and normal temperature cycle capacity retention performance of the lithium-ion batteries of Examples 1-1 to 1-20 are significantly improved. Relative to Comparative Example 3 in which the first material layer does not contain the first particles, the rate discharge capacity retention performance and normal temperature cycle capacity retention performance of the lithium-ion batteries of Examples 1-1 to 1-20 are significantly improved. Relative to Comparative Example 4 in which the first material layer is not contained, the energy density of the lithium-ion batteries of Examples 1-1 to 1-20 is significantly improved.
[0095] In particular, the lithium-ion battery prepared in the embodiment of the present application, when the mass proportion of the first particles in the first material layer satisfies 0.05≤A≤2, the lithium-ion battery rate discharge capacity retention rate, normal temperature cycle capacity retention rate and energy density are excellent. When the mass proportion of the lanthanum element in the first material layer satisfies 0.022≤B≤0.88, the lithium-ion battery rate discharge capacity retention rate, normal temperature cycle capacity retention rate and energy density are excellent. When the ratio of the mass proportion of the lanthanum element to the mass proportion of the silicon element in the first material layer satisfies 4.4≤N≤586.7, especially 20≤N≤200, the lithium-ion battery rate discharge capacity retention rate, normal temperature cycle capacity retention rate and energy density are excellent. When the ratio of the sum of the projected areas of the silicon-based particles in the first material layer to the sum of the projected areas of the carbon-based particles satisfies 1.68≤S≤100, the lithium-ion battery rate discharge capacity retention rate, normal temperature cycle capacity retention rate and energy density are excellent.
[0096] The lithium-ion batteries of the following Examples 2-1 to 2-27 differ from those of Example 1-19 only in that the thickness of the first material layer and the second material layer, the mass content of the binder in the first material layer and the second material layer, and the additive components in the electrolyte are adjusted according to Table 2. The area of the negative electrode sheet is the area of the first material layer.
[0097] Table 2
[0098]
[0099] *In the above table, the calculation results of H and K / J are rounded to 2 decimal places, and the calculation result of P is rounded to 1 decimal place; in the embodiment where graphite and hard carbon are mixed, the mass ratio of graphite:hard carbon is 1:1.
[0100] As can be seen from Table 2, the lithium-ion battery prepared in the embodiment of the present application, when the thickness relationship between the first material layer and the second material layer is regulated to meet 0.1≤H≤0.75, the lithium-ion battery rate discharge capacity retention rate, room temperature cycle capacity retention rate and energy density are all excellent. When the mass relationship of the binder in the first material layer and the second material layer is regulated to meet 0.55≤K / J≤25.6, especially 1.5≤K / J≤16, the lithium-ion battery rate discharge capacity retention rate, room temperature cycle capacity retention rate and energy density are all excellent. When the mass proportion of fluoroethylene carbonate in the electrolyte is regulated to meet 2.2≤E≤13.5, especially 5.5≤E≤11.5, the lithium-ion battery rate discharge capacity retention rate, room temperature cycle capacity retention rate and energy density are all excellent. When the mass proportion of lithium nitrate in the electrolyte is regulated to meet 0.1≤F≤8.8, the lithium-ion battery rate discharge capacity retention rate, room temperature cycle capacity retention rate and energy density are all excellent. When the area relationship among the first adhesive tape, the second adhesive tape and the first material layer is adjusted to satisfy 0.3≤P≤6, the lithium-ion battery rate discharge capacity retention rate, room temperature cycle capacity retention rate and energy density all perform well.
[0101] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modification, equivalent replacement and improvement made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A secondary battery comprising a negative electrode sheet, a positive electrode sheet, a separator and an electrolyte, characterized in that: The negative electrode plate comprises a negative electrode current collector, a first material layer and a second material layer; The first material layer includes silicon-based particles, carbon-based particles and first particles, and the first particles include lanthanum, titanium and oxygen; The second material layer is disposed between the negative electrode current collector and the first material layer; the second material layer includes graphite particles.
2. The secondary battery according to claim 1, characterized in that: Based on the mass of the first material layer, the mass proportion of the first particles is A%, and 0.05≤A≤2.
3. The secondary battery according to claim 1, characterized in that: Based on the mass of the first material layer, the mass proportion of the lanthanum element is B%, and 0.022≤B≤0.
88.
4. The secondary battery according to claim 3, characterized in that: Based on the mass of the first material layer, the mass proportion of silicon is C%, N = B / C×10 4 , 4.4≤N≤586.7, preferably 20≤N≤200.
5. The secondary battery according to claim 1, characterized in that: The surface of the negative electrode plate includes a test area. Based on the area of the test area, along a direction perpendicular to the test area, the projected area of the silicon-based particles is S1 μm 2 The projected area of the carbon-based particles is S2 μm 2 , S=S1 / S2, 1.68≤S≤100.
6. The secondary battery according to claim 1, characterized in that: The thickness of the first material layer is H1 μm, the thickness of the second material layer is H2 μm, H=H1 / (H1+H2), 0.1≤H≤0.75, preferably 0.33≤H≤0.
67.
7. The secondary battery according to claim 1, characterized in that: The first material layer and the second material layer include a binder; Based on the mass of the negative electrode plate, the mass proportion of the binder in the first material layer is K%, the mass proportion of the binder in the second material layer is J%, 0.55≤K / J≤25.6, preferably 1.5≤K / J≤16.
8. The secondary battery according to any one of claims 1 to 7, characterized in that: The secondary battery satisfies at least one of the following: (1) The silicon-based particles include a carbon carrier, elemental silicon and a carbon coating layer, wherein the elemental silicon is distributed on the surface and inside of the carbon carrier; (2) the carbon-based particles include at least one of graphite or hard carbon; (3) The first particle includes Li x La (2-x) / 3 TiO3, 0.1≤x≤0.
3.
9. The secondary battery according to any one of claims 1 to 7, characterized in that: The electrolyte includes fluoroethylene carbonate; Based on the mass of the electrolyte, the mass proportion of the fluoroethylene carbonate is E%, 2.2≤E≤13.5, preferably 5.5≤E≤11.
5.
10. The secondary battery according to any one of claims 1 to 7, characterized in that: The electrolyte includes lithium nitrate, and based on the mass of the electrolyte, the mass proportion of the lithium nitrate is F%, and 0.1≤F≤8.
8.
11. The secondary battery according to any one of claims 1 to 7, characterized in that: The positive electrode sheet and the negative electrode sheet are both provided with a tab; the positive electrode sheet, the separator and the negative electrode sheet are sequentially stacked and wound to form an electrode assembly, with the thickness direction of the electrode assembly being the first direction; the negative electrode sheet is provided with a first adhesive tape and a second adhesive tape, and the positive electrode sheet is provided with a third adhesive tape; The first adhesive tape is disposed on at least a portion of the surface of the negative electrode tab, and the third adhesive tape is disposed on at least a portion of the surface of the positive electrode tab; The projection of the second adhesive tape along the first direction at least partially overlaps with the projection of the positive electrode tab along the first direction.
12. The secondary battery according to claim 11, characterized in that: The sum of the areas of the first adhesive tape and the second adhesive tape is P1 cm 2 , the area of the first material layer is P2cm 2 , P=100×P1 / P2, 0.3≤P≤6.
13. An electronic device, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 1 to 12.